Still, the small voice : narrative, personal revelation, and the Mormon folk tradition - Mould, Tom, 1969- (Utah State University Press, 2011)
Memoratespersonal experience narratives of encounters with the supernaturalthat recount individuals' personal revelations, primarily through the Holy Ghost, are a pervasive aspect of the communal religious experience of Mormons, members of the Church of Jesus Christ of Latter-day Saints. In accordance with current emphases in folklore studies on narrative and belief, Tom Mould uses ethnographic research and an emic approach that honors the belief systems under study to analyze how people within Mormon communities frame and interpret their experiences with the divine through the narratives they share. In doing so, he provides a significant new ethnographic interpretation of Mormon culture and belief and also applies his findings directly to broader scholarly folklore discourse on performance, genre, personal experience narrative, belief, and oral versus written traditions.